Medication Safety and Pharmacovigilance in Clinical: From the Researcher Bench to the Patient Bedside (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Recent years, particularly the COVID-19 pandemic, can be considered a turning point for pharmacovigilance and pharmacoepidemiology in terms of their role in drug safety and drug utilization monitoring in clinical practice. In this context, researchers operating in the fields of pharmacovigilance and pharmacoepidemiology have extensive knowledge about approved medications, many of which have been or are currently undergoing clinical trials for repurposing. Among them, clinical pharmacologists’ knowledge can be used and translated to optimize dosing and treatment regimens and to assess the relationship between drug exposure and adverse drug events, with the crucial aims of optimizing drugs’ efficacy and ensuring drug safety in a real-world setting. Real-world data are crucial to further establish the safety profile of pharmacological treatments. As a next step, real-world data from electronic health databases may be used in pharmacovigilance and pharmacoepidemiology to monitor drug utilization patterns, as well as the efficacy and safety of drugs in large populations. Furthermore, this approach will be particularly useful for the monitoring of COVID-19 vaccines’ efficacy and safety. In this reprint, experts submited population-based studies (cohort or case–control studies), drug utilization studies, systematic reviews and meta-analyses, and review articles that contribute to improving the understanding of the role of pharmacovigilance and pharmacoepidemiology before, during, and after the COVID-19 pandemic.